Identification of various Candida species isolated from patients with vulvovaginal candidiasis attending a tertiary care hospital in North India - Jahan, Noor; Vishnoi, Pratishtha; Gupta, Bhavana; Srivastava, Swati; Ahmad, Siraj; Khatoon, Razia (International Journal of Advances in Medicine, 2020)
Background: Vulvovaginal Candidiasis (VVC) is a condition diagnosed in a large proportion of women presenting with complaints of abnormal vaginal discharge. The risk of VVC is high in women with diabetes mellitus, pregnancy, using oral contraceptives or broad-spectrum antibiotics and those having Human Immunodeficiency Virus infection. Objective of the present study was to identify the various species of Candida isolated from patients with Vulvovaginal Candidiasis. Methods: A cross-sectional study was done from January to June 2018. A total of 69 clinically suspected VVC cases were included in the study whose high vaginal swabs were collected and subjected to direct microscopy and cultured on Sabouraud Dextrose Agar (SDA). Creamy white pigmented colonies on SDA were confirmed as Candida by doing Gram’s staining. Speciation of positive cultures was confirmed by conventional methods like Corn Meal agar culture, Germ tube test (GTT), Candida CHROM Agar Medium (CAM), sugar assimilation and fermentation test. Results: Out of 69 clinically suspected VVC cases included in the study, only 14 cultures were positive for Candida species. All the 14 isolates were found to be Non-albicans Candida (NAC). Most common species isolated were Candida glabrata 7(50%), followed by Candida tropicalis 3(21.4%), Candida lusitaniae 3(21.4%), and Candida parapsilosis 1 (7.1%). Conclusions: Candida albicans was known to be the most common causative agent of VVC as it was isolated in 90% cases. However, this study showed that all isolates from VVC were Non-albicans Candida. Therefore, species identification should be done in all microbiology laboratories for accurate diagnosis of VVC.